RELATIONSHIP BETWEEN INDUSTRY BEST PRACTICES AND INFORMATION SECURITY BREACH INCIDENTS OF SACCOS IN KENYA - Sirma, Jerotich; Raburu, George; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
Information is an important organizational asset that that is mainly vulnerable to attacks fromuser error, hackers and crackers, viruses and cyber criminals. This has resulted in loss of trillionsof dollars around the world and over 4 billion shillings in East Africa. The study investigatedwhether information security policies assist in preventing unauthorized individuals fromaccessing SACCOS’ sensitive information. The study looked at the relationship betweendependent and independent variables. The study investigated the relationship between industrybest practices and information security breach incidents The study used correlational survey asits research design. The study utilized a questionnaire as a survey instrument to collect responsesfrom 85 SACCOS IT personnel with regard to their perceptions of how information securitypolicies affect computer security breach incidents. Coefficient of variation was used to determinethe sample size of 85 SACCOS registered with SASRA. Further, Simple random sampling wasused to select 85 SACCOS. From the 85 SACCOS, one IT personnel was selected using simplerandom sampling from each SACCOS to obtain 85 IT personnel from a total of 270 IT personnelfrom 135 SACCOS registered with SASRA. A pilot test was carried out to test the validity ofthe survey instrument. Cronbach’s alpha coefficient was used to assess the internal reliability ofthe research instrument. Quantitative data was analyzed by using Statistical Package for SocialSciences (SPSS) version 22. Research hypotheses were tested using both 2 tailed t-tests andanalysis of variance (ANOVA) tests. Pearson correlation was conducted to test the relationshipbetween independent variables and dependent variable. Regression analysis was used to showthe contribution of each independent variable to the dependent variable. Null hypothesis wastested at 95% level of confidence. If the p-value obtained is less than 0.05, then the nullhypothesis was rejected, but if the p-value obtained was more than 0.05, then the null hypothesiswas accepted. The results of the study revealed that there is a weak relationship betweeninformation security policies and security breach incidences in the SACCOS sector